Length-weight relationship, Fultonâ€™s condition factor and sex ratio of Bagrus docmak (ForsskÃ¥l, 1775) in Lake Chamo, Ethiopia - Shizha, Shishitu Buchale (Journal of Agriculture and Environmental Sciences, 2022)
The objectives of the study were to determine the length-weight relationship, Fultonâ€™s condition factor, and sex ratio of Bagrus docmak in Lake Chamo. Total length (TL), total weight (TW), and sex data were collected from 469 fish samples (268 females and 201 males) for one year (January to December 2021) from the commercial fishery of Lake Chamo. The collected data were summarized by using descriptive statistics (graphs and tables) and analyzed with the application of Microsoft Excel 2010 and SPSS software. The length-weight relationship was calculated using the power function and obtained as TW = 0.0087*TL3.0272, (R2 = 0.8959), TW = 0.0052*TL3.1412, (R2 = 0.9281) and TW = 0.0063*TL3.0998, (R2 = 0.9152) for females, males and combined sexes, respectively. The regression coefficient â€œbâ€ was significantly different from the cubic value â€œ3â€ (P < 0.05), implying that B. docmak of Lake Chamo followed a positive allometric growth pattern. There was a significant deviation in the sex ratio of male to female (1:1.33) from the hypothetical 1:1 ratio (Ï‡ 2 = 4.79; P < 0.05). The average Fultonâ€™s condition factor for females, males, and combined sexes was 1.01, 0.97, and 0.99, respectively. The one-way ANOVA (P > 0.05) revealed that Fultonâ€™s condition factor between sexes was insignificant. But it was significantly different in the months of interaction (ANOVA, P < 0.05). The t-test also revealed a highly significant difference in a monthâ€™s interaction (t-test, P = 0.000) indicating the seasonal variation in the mean monthly condition factor. The condition factor indicated that the health condition of B. docmak was not as good. Heavy fishing pressure and different agricultural practices were taking place around the lake which might disturb and break the chain of food availability in addition to other biotic and abiotic factors. Further investigations on water quality parameters and other biological aspects such as feeding habits and reproductive biology of B. docmak shall be undertaken for the management of the fish stocks in the lake.